If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + -3 = -23 Reorder the terms: 4(-1 + x) + -3 = -23 (-1 * 4 + x * 4) + -3 = -23 (-4 + 4x) + -3 = -23 Reorder the terms: -4 + -3 + 4x = -23 Combine like terms: -4 + -3 = -7 -7 + 4x = -23 Solving -7 + 4x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4x = -23 + 7 Combine like terms: -7 + 7 = 0 0 + 4x = -23 + 7 4x = -23 + 7 Combine like terms: -23 + 7 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 3x^2-30x+85=0 | | 15-4+6=13 | | (1/14)/420 | | (3y-5)(9+y)=0 | | 3(x-1)+4x=-24 | | 1/14/420 | | 5-8+30=12 | | 2x+17x=14+5x | | -3/4(-6x+2)=6 | | X^3+23+24=0 | | K/4+5=6 | | logx+log(x+5)=log^3 | | 2(x+2)+4x=-2 | | 3x+4y=106 | | 4ln(3x-4)=10 | | 5(x+3)-2=23 | | 7m(m-6)=2(6-m) | | 2-7(8-4x)=0 | | 4b^2-24b-11=0 | | 9+18lnx=6 | | -x^2+10=0 | | 3-9(7x+5)=4 | | (18x^2/6x^2)2 | | 2x=-2y-300 | | 4-6x+10x=-2(-5x+4) | | 25+2f=75 | | 23.1=x+1.10x | | 9+16=c^2 | | (-19)+9f=-64 | | x+2+x+7+x^2-2x+3x-3=46 | | 5b+23=63 | | 3x+4x=c^2 |